A randomized, placebo-controlled trial of aripiprazole for the treatment of methamphetamine dependence and associated psychosis - Sulaiman, A.H.; Gill, J.S.; Said, M.A.; Zainal, N.Z.; Hussein, H.M.; Guan, N.C. (2013)
Objectives. The objectives of this study were to determine the efficacy and safety of aripiprazole for treatment of psychosis, retention and abstinence in patients with methamphetamine dependence. Methods. This was a double-blind study where 37 methamphetamine dependent patients with history of psychosis were randomly assigned to receive aripiprazole (5-10 mg daily, N = 19) or placebo (N = 18) for 8 weeks. Follow-up evaluation was scheduled on day 7, 14, 28, 42 day 56 after enrolment. Results. Participants on aripiprazole were retained significantly longer in treatment (48.7 days, SD = 4.0) compared to placebo (37.1 days, SD = 5.0). The Kaplan-Meier survival analysis showed that participants on aripiprazole were less likely to drop out of the study than the placebo group (P = 0.02, x(2) = 5.3). Psychotic symptoms significantly decreased among those on aripiprazole as compared to placebo (P < 0.05). However, no statistically significance was found between the two groups in maintaining abstinence (generalised estimation equation (GEE) analysis, P = 0.41). No serious adverse events were reported in either group. Conclusion. Aripiprazole was no more effective than placebo in maintaining abstinence from methamphetamine use. However, it facilitated treatment retention and reduced the severity of psychotic symptoms. Aripiprazole was found to be generally safe and well tolerated.